La secreción cutánea, instrumento sistemático (1973)
The Author points out information lacking in morphological Systematics for evolutionary studies of amphibian taxa, relieving physiological and biochemical analysis as valuable tools of philogenetic interrelationships study.  After a brief mention of Urodela cutaneous secretion, with polypeptideshormone-like structured as chief constituent, and some steroid anuran toxic samples, there is an explanation about chromatographic isolation of indole derivatives. An important conclusion is the participation of 5-hydroxitryptaminein almost all Bufo species cutaneous secretion more concentrated when the species is more primitive; chemical affinities are represented by polygonal graphs; high affinity indexes seem to suggest us remote dispersions in earlyevolution stages; these affinities are more common between African and Tropical American Species, whereas Middle East and African Bufonidae show a low toxic affinity; Asian Bufonidae are not much analogous in cutaneous secretion composition with New World and African specimens. Actually, chemical analysis suggests some generalizations about philogenetic interrelationships and primitive spreading of early evolution specimens of anura.